The Effect Of Competence Through The Use Of Technology On Employee Performance At The South Binjai Sub-District Office - Nila Rela Ria Simanjuntak; Mesra B (International Journal of Management, Economic and Accounting, 2025)
This study aims to examine the influence of competence on employee performance with the use of technology as an intervening variable at the South Binjai Sub-district Office. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 117 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the results showing that competence has a positive and significant effect on the use of technology, shown by a T-Statistic value of 55.648 and a P-Value of 0.000. However, competence has no direct influence on employee performance, with a T-Statistic value of 0.007 and a P-Value of 0.995. On the contrary, the use of technology directly has a positive and significant effect on employee performance with a T-Statistic value of 7.873 and a P-Value of 0.000. The findings also show an indirect influence between employee competence and performance through the use of technology as an intervening variable, with a T-Statistic value of 7.475 and a P-Value of 0.000. The implications of this study suggest that organizations prioritize competency development and access to the right technology to optimize employee performance. The study also prompted further studies of other intervening variables, such as organizational culture or psychological capital, that could strengthen the relationship between competence and performance.